Improving Fine Motor Skills in Children with Special Needs Through Foam Squeezing Play Therapy - Ferasinta Ferasinta; Titin Hidayatin; Endah Zulya Dinata; Andry Sartika (Health and Technology Journal (HTechJ), 2024)
The development of children with special needs (ABK) has obstacles in terms of fine motor development. Like the ability to play the foam squeezing game. This research method uses quasi-experiment, namely providing intervention to children. A sample of 15 children was taken using purposive sampling according to the inclusion criteria. The research results obtained in the intervention group before and after foam massage play therapy obtained a p-value of 0.000. The discussion in the research found the effect of foam squeezing play therapy on improving the fine motor skills of children with special needs. It is recommended that SDLB Negeri 4 Bengkulu be more creative and use varied learning methods such as squeezing foam so that children's fine motor skills are more stimulated.